Analisis Peran Lingkungan Sekolah dalam Mendukung Hasil Belajar Siswa Sekolah Dasar - Siti Mafridatul Mahbubah; Didit Darmawan (LP3M IAI Al Urwatul Wutsqo Jombang, 2026)
This study aims to comprehensively analyze the influence of the school environment on elementary students’ learning outcomes through a literature review approach. The method employed is a systematic literature review following PRISMA guidelines in the process of identifying, selecting, and evaluating relevant scholarly articles from academic databases such as Google Scholar, Scopus, and Web of Science. The inclusion criteria consist of publications within the last ten years, topic relevance, and adequate methodological quality. The data were analyzed using content analysis to identify key themes related to the physical, social, and psychological aspects of the school environment. The findings reveal that the school environment has a significant influence on students’ learning outcomes, both directly and indirectly through the enhancement of motivation and learning engagement. A supportive school environment contributes to the creation of effective, interactive, and meaningful learning experiences. Furthermore, the interaction between environmental factors and internal aspects such as students’ interest and motivation plays a crucial role in determining academic achievement. This study provides theoretical contributions by enriching the discourse on external factors in learning and offers practical implications for policymakers in designing optimal learning environments